AB0433 HIGH RISK OF MATERNAL THROMBOTIC AND SEVERE HEMORRHAGIC COMPLICATIONS IN 119 PROSPECTIVE PREGNANCIES ASSOCIATED WITH ANTIPHOSPHOLIPID SYNDROME (GR2 STUDY). (2nd June 2020) - Murarasu, A.; Le Guern, V.; Guettrot Imbert, G.; Pasquier, E.; Yelnik, C.; Queyrel, V.; Schleinitz, N.; Ferreira-Maldent, N.; Langlois, V.; Urbanski, G.; Deneux-Tharaux, C.; Costedoat-Chalumeau, N.
Abstract : Background: Women are at higher risk of thrombotic or severe bleeding complications during pregnancy, especially in the postpartum period (around 1%), but no prospective data have been available for women with antiphospholipid syndrome (APS). We report the first results of the French GR2 prospective study of pregnancy and rare diseases. Objectives: To describe the thrombotic and haemorrhagic events in APS patients included in the GR2 study and to identify risk factors associated with these complications. Methods: Women with APS and an ongoing pregnancy at 12 weeks of gestation were eligible for prospective inclusion in the GR2 study. Exclusion criteria were proteinuria (ratio > 1 g/g), serum creatinine > 100 µmol/L, or a multifetal pregnancy. Severe bleeding was defined as the need for transfusion, intensive care admission, or invasive treatment. Uteroplacental vascular insufficiency was defined as intrauterine growth restriction, preeclampsia, or HELLP syndrome. Results: The study included 119 pregnancies in 119 APS patients (53% thrombotic and 47% obstetric only APS). Treatment included aspirin (99%) and heparin (98%, in the therapeutic range for 50%). Twelve women (10%) had a thrombotic (n=5) and/or a severe haemorrhagic event (n=9). The thrombotic events included stroke (at 11 weeks; n=1), catastrophic APS (CAPS) (n=2), a pulmonary embolism (n=1), and portal vein thrombosis (n=1)(in the postpartum). Placental insufficiency was also present in 6 of these 12 women. Among the 22 (18.5%) women with at least one bleeding event (n=28), 9 (7.6%) had events defined as severe. Six of nine (67%) severe haemorrhages occurred in the postpartum and were directly related to the delivery. Two required an intrauterine balloon tamponade, two uterine arterial embolisation, and three surgery, including one hysterectomy. No women died. Finally, thrombotic and/or severe bleeding events during the postpartum period (n=9) were more frequent in women with lupus anticoagulant (14% versus 0%; P=0.01), with associated placental insufficiency (29% versus 3%; P=0.001) and with preterm delivery ≤34 weeks (33% versus 4%, P=0.002). Conclusion: Even though most women in our cohort received treatment based on current recommendations, a substantial number of maternal thrombotic and haemorrhagic events (10%) occurred. Despite several life-threatening complications, including CAPS, no women died. Most of the thrombotic or haemorrhagic events occurred in the peripartum period, and they were more frequent in women with the lupus anticoagulant, placental insufficiency, and preterm delivery. Although this morbidity rarely appears preventable, knowledge of the risk factors should increase awareness and help physicians to manage APS patients at particularly high risk. Disclosure of Interests: Anne Murarasu: None declared, Véronique LE GUERN Grant/research support from: UCB for GR2 study (to our institution), Gaêlle Guettrot Imbert: None declared, Elisabeth Pasquier: None declared, cecile yelnik: None declared, Viviane Queyrel: None declared, Nicolas Schleinitz: None declared, Nicole Ferreira-Maldent: None declared, Vincent Langlois: None declared, Geoffrey Urbanski: None declared, Catherine Deneux-Tharaux: None declared, Nathalie Costedoat-Chalumeau Grant/research support from: UCB to my institution